Temboro Tablighi Jamaat's Reception to Hadith on Covid-19 - Zuhri Qudsy, Saifuddin; Awwabin, Muhammad Rosyid; Sholahuddin, Ahmad (DINIKA : Academic Journal of Islamic Studies, 2020)
Tablighi Jamaat (TJ) has recently been in a global spotlight as it is considered to cause a new cluster of Covid-19 cases to occur. According to some news reported by various media, Tablighi Jamaat remained in their ignorance of the pandemic. This may partly result from the way of interpreting religious texts. This article aims to discuss the views of the Temboro Tablighi Jamaat, Magetan, East Java about Covid-19, the factors that shape their understanding, and their religious activities during the Covid-19 pandemic. This article shows that the followers of Tablighi Jamaat in Temboro, Magetan, East Java, view diseases from the point of view of sharia (exoteric path) and haqiqa (mystcal truth). From the point of view of haqiqa, they see the disease as something that naturally comes from Allah. Meanwhile, adopting the point of view of Sharia, they try to replicate the way the Prophet Muhammad when he dealt with illnesses, which is documented in the hadith about the plague (tha’un). This reflects two reception models, namely exegetical reception and functional reception. This understanding then changed the TJ followers’ way of conducting their activities during the Covid-19 pandemic. Their implementing health protocols and setting reasonable restrictions on the activities they usually perform in normal conditions. Therefore, this article also denies the statements of media about the ignorance of TJ followers in Temboro as to the Covid-19 pandemic.